Low-cost and portable ground station for the reception of NOAA satellite images - Quiroz Olivares, Antony (2019)
Currently, in Peru, the study of satellite images is increasing because it has the Earth observation satellite PeruSat-1. However, the cost of implementing a ground station is very high; for this reason, it is baffling that each university has its station. In the present work, the design and implementation of a low-cost portable earth station for the reception of meteorological satellite images is proposed in an automatic way, using accessible electronic devices such as Raspberry Pi 3b +, Software Defined by Radio (SDR) and an antenna double cross four dipoles, in this way encourage the study of satellite images in schools and universities. The results obtained show the viability of this project.